PENGEMBANGAN MEDIA SAINS BERBASIS GAME EDUKASI PADA MATERI TATA SURYA - Tomy Arifin; Undang Rosidin; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2015)
This study aimed to create a science media based on education game that was integrated by facebook site on solar systems material of junior high school class VIII, as well as to determine the attractiveness, easiness, and effectiveness of science media based on educational game that was integrated with facebook. The research development model used the modified instructional development model with the following phases: requirements analysis, resource identification, identification of product specifications, product development, internal testing, external testing, production. The results showed that science media based on education game is attractive with average score of 3.05 , easy with score of 3.00, and useful with score of 3.15. Based on the results of effectiveness test, 85% of students achieve a minimum standard of completeness specified criteria, it indicated that science media as a results of development was effective to use as learning media.Penelitian ini bertujuan untuk menciptakan media sains berbasis game edukasi yang diintegrasikan dengan situs facebook pada materi tata surya SMP kelas VIII, serta untuk mengetahui kemenarikan, kemudahan dan efektifitas media sains berbasis game edukasi yang diintegrasikan dengan situs facebook. Model penelitian pengembangan ini menggunakan model pengembangan Instruksional termodifikasi dengan tahap-tahap berikut: analisis kebutuhan, identifikasi sumberdaya, identifikasi spesifikasi produk, pengembangan produk, uji internal, uji eksternal, dan produksi. Hasil penelitian menunjukkan bahwa media sains berbasis game edukasi menarik dengan skor rata-rata kelas sebesar 3,05, mudah dengan skor 3,00, bermanfaat dengan skor 3,15. Hasil uji keefektifan menunjukkan, 85% siswa mencapai standar kriteria ketuntasan minimal yang ditetapkan, sehingga media dinyatakan efektif untuk digunakan sebagai media belajar.Kata kunci : game edukasi, media sains, pengembangan, tata surya.